Analisis Strategi Pengadaan Palm Kernel Expeller pada PT X - Handayani, Fitrah; Budipriyanto, Adi (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
This research is based on case study aims to identify ongoing PKE procurement strategy in PT X, to capture the problem along with its cause and the impact itself for the company. This research also tries to develop the more relevant procurement strategy to company’s necessity. The method in this research is qualitative descriptive through data analysis derived from in depth interview, field observation, also documentation. Current PKE procurement strategy in PT X still not able to accommodate customer’s need hence cause losses due to instability quantity amount of supply. Procurement strategy development by creating consolidation warehouse aims to mitigate the problem risk in PKE procurement with its cost consideration.